Hubungan Aromaterapi Frangipani terhadap Peningkatan Kualitas Tidur pada Remaja - Regina Valerie; I Made Niko Winaya; Ni Wayan Tianing (Jurnal Syntax Admiration, 2024)
Adolescents are individuals who are in a period of purbetas where there will be many changes such as the way of behavior and lifestyle. Insomnia is a condition that is often experienced by teenagers. Based on the National Sleep Foundation, the prevalence of insomniacs in Indonesia reaches 70%. Aromatherapy frangipani is one therapy that can relax so that the body can fall asleep. Frangipani contains triterpenoid compounds, amyrin, geraniol, citronellol, and linalool which can provide a relaxing effect. This research study aims to determine the relationship between the use of aromatherapy frangipani to improve sleep quality in adolescents. Research in this study uses literature review studies or literature reviews compiled using secondary data in the form of studies of research journals obtained from various scientific journal databases on the internet related to the relationship of aromatherapy use to improve sleep quality. The results, from 4 articles discussing the benefits of aromatherapy on improving sleep quality all showed that there was a significant influence between aromatherapy and the incidence of insomnia or improved sleep quality in adolescents. Bottom Line: Aromatherapy has a significant relationship to improved sleep quality and may reduce insomnia. The quality of adolescent sleep can be disrupted can be caused by various factors such as lifestyle, drugs, smoking, and stress in anxiety disorders.